Pengaruh Terapi Relaksasi Otot Progresif Terhadap Penurunan Tingkat Stres pada Mahasiswa Keperawatan Stikes Guna Bangsa Yogyakarta: The Effect of Progressive Muscle Relaxation Therapy on Reducing Stress Levels in Students of Nursing Stikes Guna Bangsa Yogyakarta - Safitri Dara; Rista Islamarida; Shanti Wardaningsih (Journal of Health, 2024)
Students are part of the academic community in a tertiary institution which often has problems that pose a heavy psychological risk. High demands on nursing students often cause academic stress. Handling stress can be done in medical and non-medical ways. One of the non-medical therapies that can be done is progressive muscle relaxation techniques. To determine the effect of progressive muscle relaxation therapy on reducing stress levels in STIKES Guna Bangsa Yogyakarta nursing students. This study uses the Quasi Experiment model Nonequivalent control group design. The population was nursing students at STIKES Guna Bangsa Yogyakarta with a sample of 36 respondents who were divided into intervention and control groups. The sampling technique used random sampling. The measuring tool used is the student-life Stress Inventory (SSI) questionnaire. Bivariate test using parametric paired t-test. The stress level in the intervention group before the intervention was in the low stress category of 50.0% and after the intervention was in the low stress category of 61.1%. The stress level in the control group at the beginning of the measurement was in the low stress category of 50.0% and at the end of the measurement was in the moderate stress category of 50.0%. The results of the analysis test using the paired sample T-test in the intervention group showed a significance of 0.000. While in the control group showed a significance of 0.310. There is an effect of progressive muscle relaxation on reducing stress levels in STIKES Guna Bangsa Yogyakarta nursing students